A Study of Emerging Trends and Challenges in Air-Conditioning Industry in India - Shukla, Kedar; Raut, Amol (Indian Journal of Marketing, 2010)
In a ’hot’ climate country like India, we have a common meaning or conventional understanding of the term ’Air-conditioning’ which is ’Cooling the air’. However, Air-conditioning as per its technical definition is a... "Process of cooling or heating, cleaning, humidifying or dehumidifying air and distributing the air at proper velocity to achieve desired inside conditions." Today, air-conditioning has become a ’need’ of modern day life in contrast to its earlier perception as a ’luxury’ 6-8 years back. Although ’air-conditioners’ or the ’air-conditioning systems’ are still high energy consuming devices, certain facts like increase in the purchasing power of people with the economic growth in the India, government initiatives like lowering taxes and duties, liberalization of fiscal policies in terms of foreign direct investment (FDI) etc. has given a boost to the industry and as a result, the industry is expected to grow at Rs. 38,000 Crore by the end of 2012. (Estimate, from Financial Report 2008: Blue Star Limited).